Kondisi Pencemaran Udara pada Saat Periode Lebaran 2022 di Wilayah Jakarta - Nur Faris Prih Waryatno; Nanda Putri Kinanti; Taryono (Stasiun Pemantau Atmosfer Global Lore Lindu Bariri - Palu, 2022)
Particulate Matter is part of air pollution and as an indicator of air pollution in an area that can cause environmental damage and health problems in living things. The reduction of human activities in the DKI Jakarta area during big days such as during the Eid holidays is suspected to make air quality below the threshold value during normal conditions. So this research aims to determine the condition of air quality, especially particulates during the period before, during and after Eid al – Fitr 2022 in the Jakarta area. The PM2.5 concentration data used is observation data at BMKG observation points in Kemayoran and Airnow (Gambir, Kebayoran), while the rainfall data used is BMKG observation post data in Kemayoran and South Jakarta. The method used in this study is descriptive analysis. From the results of the analysis, it was found that the PM2.5 observation location showed a high concentration value one day before Eid which was related to the increase in motor vehicle use. However, there was a decrease in PM2.5 concentrations during Eid and one day after Eid, this was related to the decrease in the use of motor vehicles in the region and was accompanied by rain events that acted as washing the atmosphere. In the Kebayoran Baru – South Jakarta area, the highest concentration decreased by up to 51%.